Reprocessing of UV-weathered wood flour reinforced polypropylene composites: Study of a natural outdoor exposure. (November 2016) - Soccalingame, L.; Perrin, D.; Bénézet, J.-C.; Bergeret, A.
Abstract: This work aims to determine and understand the influence of a one-year natural UV weathering on the reprocessing of a wood-plastic composite (WPC), i.e. a wood flour reinforced polypropylene (PP) composites. Two wood flour contents (10% w/w and 30% w/w) were studied in comparison to neat PP. Injected samples of were submitted to a long-term natural outdoor exposure followed by one complete reprocessing cycle (grinding then injection). The visual aspect evolution of the surface was followed by optical microscopy. In order to understand the material physical degradation, the mechanical behaviour was measured thanks to tensile and Charpy impact tests. The assessment of the microstructural evolution was performed by differential scanning calorimetry (crystallinity ratio), rheological tests (viscosity), size exclusion chromatography tests (average molecular weights) and infrared spectroscopy analysis (chemical structure). A "regeneration" phenomenon was highlighted as mechanical properties are recovered after reprocessing. This is due to the mixing and the dilution of the degraded chains into the material as no recombination or crosslinking mechanism was detected. A comparison with an artificial UV weathering performed on the same samples and exposed in a previous study was finally investigated.